High performance thin layer chromatographic determination of erythromycin in pharmaceutical preparations - Liawruangrath B. (2014)
A high performance thin layer chromatographic method was developed for the determination of erythromycin. The drug was separated on a silica gel 60 plate and developed in methanol by means of an automatic multiple development. The chromatogram was sprayed with 10% sulphuric acid solution and heated at 100°C for 10-15 minutes. The area of the spot was quantified by a TLC scanner at a wavelength of 410 nm. A linear calibration curve was established over the range of 4-6 μg in 10 μL of erythromycin. The relative standard deviation for five replicate determinations was found to be 1.45% for 5 μg in 10 μL of erythromycin standard. The average percentage recovery was found to be 99.87. The method has been applied to the determination of erythromycin in various pharmaceutical dosage forms. Common excipients in formulations do not interfere. After optimizing the solvent system, it was found that the use of silica gel 60 F254 TLC plate with a DVS composed of ethyl acetate, ethanol and 10% sodium acetate pH 9.5 (9:7:8) led to the differentiation and quantitation of erythromycins A, B and C with an R.S.D. of less than 2.0%. The method is simple, precise and inexpensive. It should be used for routine analysis.